Analysis Of The Influence Of Digital Competency On The Effectiveness Of Technology-Based Training - Afrianda, Raditya Eka; Takih, Takih (Lentera Ilmu Nusantara, 2024)
An analysis of the influence of digital competencies on the effectiveness of technology-based training in employees at the operator level shows that the adoption of Industry 4.0 technology has a significant impact on the operator learning process. A study conducted on the training of new operators at quality inspection stations showed that operators supported by I4.0 technology had a higher learning rate compared to those who performed the same task without I4.0 supportThis study is categorized as a survey research because it collects information from respondents using questionnaires/questionnaires from the objects studied. The data collection method in this study was carried out using a questionnaire as the main instrument. The questionnaire was distributed to respondents who had been determined according to the research criteria. The sampling technique used is non-probability sampling with the purposive sampling method. The questionnaire consists of two main parts. The first part contains questions about the respondents' demographic data, such as age, gender, and length of work. The second part contains a statement that measures the research variables, namely Digital Competence and Technology-based Training Effectiveness. The statements on the questionnaire were compiled using a 5-point Likert scale, which allowed respondents to give answers in the range of strongly disagreeing (1) to strongly agreeing (5). The digital competence of employees at the operator level at PT Frisian Flag Indonesia has a significant positive influence on the effectiveness of technology-based training. Digital competencies that include technological literacy, application mastery, and the ability to operate technological devices allow employees to better absorb training materials. However, the influence of digital competence tends to be smaller than other factors, such as the position level.